Collaborative Writing Activity Using Google Docs: Non-English Major Students Perspectives and Difficulties - Nurul Hidjrah Hairuddin (SELTICS, 2020)
One of the most challenging skills for non-English major students is writing an essay since they have to pay attention to the language structure and must be able to transfer their thoughts and ideas into the target language. In regard to solving this problem, regular change and development are needed in teaching English writing. One of the methods that increased to be used is collaborative writing using Google Docs. This study aims to investigate the non-English major students’ perspectives and difficulties in collaborative writing through Google Docs. This study examined 22 students from a state polytechnic in Makassar who have involved in collaborative writing activity through Google Docs. A convergent parallel design was applied in this study, where the data collected by using a questionnaire which consists of closed- open-ended questions and interview. The closed-ended questions data were analyzed quantitatively using descriptive statistic with SPSS. Further, the collected data from the open-ended questions and the interview was analyzed qualitatively using a narrative method. The results show that the students have positive perspectives on collaborative writing activity through Google Docs and did not encounter many difficulties when they were involved in this activity.